β-Hydroxy-β-methylbutyrate (HMB) supplementation in prevention and treatment of elderly sarcopenia. - Cieślak, Dominika; Zarobkiewicz, Michał; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2018)
β-Hydroxy-β-methylbutyrate (HMB) is a leucine metabolite, naturally appearing in human body. Both leucine and HMB are believed to be potent protein synthesis enhancers in skeletal muscles. The current articles reviews and summarizes findings from original studies on the possible therapeutic role of HMB in elderly sarcopenia. HMB seems to be capable of not only preventing, but also reversing sarcopenia. Five main effects on skeletal muscles have been noted: 1) inhibition of protein breakdown and thus lower muscle degradation, 2) increased endoplasmic reticulum calcium release, 3) lower fat content in skeletal muscle, 4) increased oxygen metabolism, 5) stimulation of satellite cells and thus muscle regeneration. Therefore, HMB emerges as potentially useful agent in treating and preventing sarcopenia.